From Observability to Closed-Loop AIOps: Data-Driven Automation for Secure and Resilient Network Operations - Mohit Bajpai (The Eastasouth Journal of Information System and Computer Science, 2023)
Modern enterprise and service-provider networks are now distributed across cloud, edge, software-defined data centers, mobile access, Internet of Things (IoT), and hybrid work environments. The operational challenge is no longer limited to device availability; teams must interpret high-volume telemetry, fast-changing application paths, user-experience signals, identity context, security events, and configuration drift at machine speed. This updated article expands the original discussion of AI Ops, machine learning, observability, and network security by adding a data-centered reference architecture, operational metrics, model-selection considerations, security controls, deployment phases, and governance requirements. The article explains how telemetry from SNMP, streaming telemetry, NetFlow/IPFIX, syslog, OpenTelemetry, endpoint logs, cloud logs, configuration repositories, and security tools can be converted into actionable intelligence through anomaly detection, forecasting, causal correlation, risk scoring, and policy-based automation. It also positions closed-loop AIOps as a practical operating model that improves mean time to detect, mean time to acknowledge, mean time to resolve, service-level compliance, capacity planning, and security response while preserving human approval for high-risk actions.